2018
DOI: 10.1186/s13023-018-0794-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased outlet angle of the superior cerebellar artery as indicator for dolichoectasia in late onset Pompe disease

Abstract: BackgroundLysosomal α-glucosidase deficiency (Pompe disease) not only leads to glycogen accumulation in skeletal muscle, but also in the cerebral arteries. Dolichoectasia of the basilar artery (BA) has been frequently reported. Therefore progression of BA dolichoectasia in late onset Pompe patients (LOPD) was studied.MethodsBA length, diameter and volume, and cerebral lesions were analysed by MRI/TOF-MR angiography or CT/CT angiography in 20 LOPD patients and 40 controls matching in age, sex- and cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…We agree with Finsterer that LOPD has most likely an impact on cerebral pathology since glycogen storage occurs in cerebral vessels and brain tissue which is not reachable by the current ERT. In fact, our previous studies [10] and others confirm prominent vertebrobasilar ectasia in LOPD patients [6].…”
supporting
confidence: 53%
“…We agree with Finsterer that LOPD has most likely an impact on cerebral pathology since glycogen storage occurs in cerebral vessels and brain tissue which is not reachable by the current ERT. In fact, our previous studies [10] and others confirm prominent vertebrobasilar ectasia in LOPD patients [6].…”
supporting
confidence: 53%
“…LOPD patients of this study also revealed balance deficiencies in visual and nigrostriatal regulation, cerebellar regulation, and in the vestibular subsystem with various interactions between the subsystems. This reflects the multi-systemic nature of Pompe disease since there are reports about cerebral [35,36] and vestibulocochlear affections [37] in LOPD patients. However, visual function has not yet been found when analyzed by evoked potentials [38].…”
Section: Discussionmentioning
confidence: 77%
“…Particular attention to the tongue while reviewing brain MRIs may be a crucial clue for the diagnosis of muscle weakness in adult LOPD patients [ 45 ]. Dolichoectasia of the basilar artery (BA) is the most striking cerebrovascular finding in adult LOPD patients as Pompe disease is associated with BA dilation, elongation, and elevated bifurcation height of the BA, resulting in cerebrovascular complications [ 46 ]. Therefore, neurologists should recommend a computer tomography angiography or a magnetic resonance angiography in adult LOPD patients for early detection of cerebrovascular malformations as these could lead to life-threatening events such as subarachnoid hemorrhage or brainstem compression [ 33 ].…”
Section: Discussionmentioning
confidence: 99%